Renegotiating tasks or goals as rupture repair: A task analysis in a cognitive–behavioral therapy for personality disorder. - Muran, J. Christopher; Eubanks, Catherine F.; LIPNER, Lauren M.; Bloch-Elkouby, Sarah (Psychotherapy Research, 2023)
The purpose of this study was to provide some definition of rupture repair in a cognitive–behavioral therapy (CBT) for personality disorders, specifically how treatment tasks or goals are renegotiated. Following a task analysis, a rational model was developed with the support of an expert panel. An empirical analysis was conducted on six CBT cases sampled from a clinical trial that included personality disordered patients and treatment adherent therapists. Two sessions from each case indicating rupture repair were selected, based on patient and therapist ratings of the Working Alliance Inventory—12 item version (WAI-12) and rupture presence. A qualitative analysis of the sessions was conducted with the support of the observer-based Rupture Resolution Rating System (3RS—2022). The empirical analysis provided some support for many of the stages defined in the rational model, but less support for the hypothesized sequences of stages. A rational-empirical synthesis yielded a revised model that suggested therapists combine various strategies in rupture repair in a variety of ways, not necessarily in consistent sequences. The renegotiation of tasks and goals in this CBT sample was variable. The importance of responsiveness and the need to validate the rational-empirical model were highlighted.